"As Needed" nonvitamin K antagonist oral anticoagulants for infrequent atrial fibrillation episodes following atrial fibrillation ablation guided by diligent pulse monitoring: A feasibility study. (4th February 2019) - Zado, Erica S.; Pammer, Monica; Parham, Tara; Lin, David; Frankel, David S.; Dixit, Sanjay; Marchlinski, Francis E.
Abstract: Introduction: After atrial fibrillation (AF) ablation, oral anticoagulation (OAC) is recommended if stroke risk as assessed by CHA2 DS 2 ‐VASc score is high. However, patients without AF are often reluctant to take daily OAC. We describe outcome using as needed nonvitamin K antagonist (NOACs) guided by pulse monitoring to detect AF following successful ablation. Methods and Results: We identified 99 patients (84% male, age 64 ± 8 years), CHA2 DS 2 ‐VASc score greater than or equal to 1 in men and greater than or equal to 2 in women (median 2, range 1‐6), capable of pulse assessment twice daily and no AF on extended monitoring after AF ablation. All patients were instructed to start NOAC if AF >1 hour or recurrent shorter episodes. Duration of NOAC use after restart was typically 2 to 4 weeks. After 30 ± 14 months (total 244 patient‐years), 22 patients (22%) transitioned to daily NOAC because of noncompliance with pulse assessment or patient preference (six patients) or because of suspected or documented AF episode(s) in 16 (16%) patients. Of the remaining 77 (78%), 14 (14%) used NOACs but did not transition back to daily use, most (10 patients) with single use (seven patients) or non‐AF rhythm (three patients) documented. There was only one thromboembolic event (0.4%/yr of follow‐up) in patient without AF and one mild bleeding event (epistaxis). Conclusion: The use of as needed NOACs when AF is suspected with pulse monitoring is effective and safe to maintain low risk of stroke and bleeding after successful ablation. Transition back to daily NOAC use should be anticipated in about one quarter of patients.